Efektivitas Pelatihan “Cohesion Hub” untuk Menurunkan Social Loafing pada Anggota UKM Setingkat Universitas Negeri Padang - Ananda, Fitri Tri; Lusiria, Devi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine whether Cohesion Hub training, based on group cohesiveness theory, is effective in reducing social loafing among members of a UKM at Padang State University. This study was a quasi-experimental study with a Pretest-Postest Control Group Design. Data analysis used an independent sample t-test with the JASP application. The sampling technique used purposive sampling. The subjects were 34 UKM members, divided into 17 experimental groups and 17 control groups. The experiment was conducted over two days. The results of this study indicate that H1 is accepted and H0 is rejected. This is supported by an independent sample t-test with a p-value of 0.001 < 0.05. Therefore, it is concluded that the Cohesion Hub training has proven effective in reducing social loafing among UKM members at Padang State University.